Leaf photosynthesis is positively correlated with xylem and phloem areas in leaf veins in rice (Oryza sativa) plants. (10th February 2022) - Huang, Guanjun; Shu, Yu; Peng, Shaobing; Li, Yong
Abstract: Background and Aims: Leaf structure is an important determinant of leaf photosynthesis; however, the impacts of leaf structural traits on gas exchange parameters are still not fully understood. In the present study, 11 rice genotypes were grown in pots to investigate the influence of leaf structural traits on leaf photosynthesis and hydraulic conductance ( K leaf ). Methods: In this study, leaf photosynthetic rate ( A ), stomatal conductance ( g s ), mesophyll conductance and K leaf were measured. In addition, leaf structural traits including leaf thickness (LT), leaf mass per area and leaf xylem and phloem sizes were also measured to investigate their impacts on rice photosynthesis. Key Results: We found that the total area of xylem conduits per major vein ( X major ), leaf phloem area per minor vein ( P minor ) and LT were positively correlated with K leaf, g s and A . The path analysis suggested that, however, only P minor had a direct impact on A ; X major had an indirect impact on A via g s and P minor, while LT did not show any direct or indirect impact on A . Conclusion: This study highlighted the importance of manipulations in X major and P minor, two previously overlooked leaf traits, to improve leaf photosynthesis in rice plants.